Blind SINR estimation for OFDM system in the presence of radio frequency interference - Shun-li HONG; You-ming LI; Ming JIN; Gang WANG (Tongxin xuebao)
Based on cyclostationarity properties of OFDM signal, a novel blind SINR estimation method for OFDM sys-tem in the presence of RFI was proposed. By analyzing the power distribution of cyclic correlation of transmitted signal, RFI and AWGN, appropriately selecting the time delay variable and cyclic frequency of the OFDM signal, the signal and interference plus noise power could be efficiently isolated in the power domain, which formed the SINR estimation method. Computer simulation results verify that the performance of the proposed method is superior to that of sec-ond-order and fourth-order moments (M2M4) method and the complexity of the new method is also lower than that of the M2M4 method. The new method can also effectively estimate SINR under the fast fading Rayleigh channel. Furthermore, the new method is robust to the density of RFI signal.